2003
DOI: 10.1046/j.1472-4642.2003.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of nonparametric species richness estimators in a high diversity plant community

Abstract: The efficiency of four nonparametric species richness estimators first-order Jackknife, second-order Jackknife, Chao2 and Bootstrap was tested using simulated quadrat sampling of two field data sets (a sandy 'Dune' and adjacent 'Swale') in high diversity shrublands (kwongan) in south-western Australia. The data sets each comprised > 100 perennial plant species and > 10 000 individuals, and the explicit (x-y co-ordinate) location of every individual. We applied two simulated sampling strategies to these data se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
15

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 37 publications
4
135
0
15
Order By: Relevance
“…A riqueza de espécies esperada para Q1 e Q2 e para T1 e T2, foi calculada usando o estimador de riqueza Jackknife de primeira ordem, que prevê o número de espécies em uma área com base na frequência das espécies encontradas nela, ou seja, projeta o número total de espécies a partir da heterogeneidade da amostra (Chiarucci et al 2003).…”
Section: Análise Dos Dadosunclassified
“…A riqueza de espécies esperada para Q1 e Q2 e para T1 e T2, foi calculada usando o estimador de riqueza Jackknife de primeira ordem, que prevê o número de espécies em uma área com base na frequência das espécies encontradas nela, ou seja, projeta o número total de espécies a partir da heterogeneidade da amostra (Chiarucci et al 2003).…”
Section: Análise Dos Dadosunclassified
“…The real debate is about choosing the best estimator for a particular study, taxonomical group or data set. This is a controversial issue, still under study, because different authors reach different conclusions on which is the best estimator, as shown by contrasting results obtained in their studies by, for example, Colwell and Coddington (1994); Walther and Morand (1998); Chiarucci et al (2003); Foggo et al (2003) and Hortal et al (2006). Therefore, until more conclusive information is available, checking the suitability of several estimators seems a convenient starting point when studying little known communities.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of them, ACE, ICE, Chao 1, Chao 2, Jackknife 1, Jackknife 2, Bootstrap, MMRuns and MMMeans were calculated with the software EstimateS version 7.0 (Colwell, 1997). They have all been widely used and studied (Chazdon et al, 1998;Brose et al, 2003;Chiarucci et al, 2003). Chao 1 and Jackknife 1 are designed to estimate richness from single samples while the rest require several samples.…”
Section: Selection and Calculation Of Richness Estimations Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking for the four richness estimators they performed differently, Jackknife 1 and Chao 1 generating large estimates of species richness, Bootstrap giving a lower estimate of species richness and Michaelis-Menten mean (MMMean) clearly underestimating species richness. Since the available estimators are probably underestimating true species richness in most studies (Chiarucci et al, 2003), all but Michaelis-Menten mean estimator gave probably realistic estimates of species richness. This contrasts with the study of Toti et al (2000), in which Chao 1 gave unrealistic large estimates and MMMean performed better.…”
Section: Sampling Efficiency Richness Estimators and Accumulation Cumentioning
confidence: 97%